2000
DOI: 10.1590/s0034-71082000000100011
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and net primary production of the aquatic macrophite Nymphaea rudgeana C. F. Mey in a lotic environment of the Itanhaém River basin (SP, Brazil)

Abstract: In this paper we evaluated the population dynamics and obtained estimates of the net primary production of the aquatic macrophyte Nymphaea rudgeana in an arm of the Itanhaém River (São Paulo State, Brazil). This species presents, in the studied area, a broad seasonal variation of biomass. As from November (13.1 g DW/m 2 ) we observed a gradual increase of biomass that reached a maximum in February (163.1 g DW/m 2 ). Then, the biomass decreased, maintaining low levels until a new growth period. The reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 4 publications
(6 reference statements)
1
14
0
3
Order By: Relevance
“…However, this simulated annual figure is comparable with what Trimmer et al [44] reported for the River Frome (0.56 kg C m −2 year −1 ) and indicates a moderately productive stream when compared with other studies (e.g. Brazil, 0.3-0.38 kg C m −2 year −1 [50]; Spain, 13 kg C m −2 year −1 [51]). Macrophytes were always the single dominant primary producers except in autumn, when epiphytes and sediment algae were similarly productive.…”
Section: Primary Producer Dominance and Environmental Thresholds In Tsupporting
confidence: 89%
“…However, this simulated annual figure is comparable with what Trimmer et al [44] reported for the River Frome (0.56 kg C m −2 year −1 ) and indicates a moderately productive stream when compared with other studies (e.g. Brazil, 0.3-0.38 kg C m −2 year −1 [50]; Spain, 13 kg C m −2 year −1 [51]). Macrophytes were always the single dominant primary producers except in autumn, when epiphytes and sediment algae were similarly productive.…”
Section: Primary Producer Dominance and Environmental Thresholds In Tsupporting
confidence: 89%
“…Numerous authors [11,21,32,[43][44][45][46] have emphasized that there is a direct relationship between the primary production dynamics of macrophytes and light regime, temperature, water depth, sediment composition and the amount of available nutrients. Here we show that these ecological factors affected the primary production in Lake Provala.…”
Section: Discussionmentioning
confidence: 99%
“…1) is influenced by a tidal regime with a mixture of freshwater and saltwater that sets a salinity gradient in the rivers (Camargo et al, 2002). The study area is characterized by a small seasonal variation in climate (mean summer precipitation = 256.4 mm and mean winter precipitation = 92.7 mm; mean summer temperature = 27.9°C and mean winter temperature = 21.1°C) and limnologic characteristics, the absence of seasonal flooding pulses, a small change in the water level due to micro-tides (maximum tidal amplitude of 1.50 m) and rainfall in short time periods (Camargo & Florentino, 2000).…”
Section: Study Areamentioning
confidence: 99%